Randomized study combining interferon and glatiramer acetate in multiple sclerosis. Issue 3 (11th March 2013) - Lublin, Fred D.; Cofield, Stacey S.; Cutter, Gary R.; Conwit, Robin; Narayana, Ponnada A.; Nelson, Flavia; Salter, Amber R.; Gustafson, Tarah; Wolinsky, Jerry S.; ,
<x xml:space="preserve">Abstract</x> Objective A double‐blind, randomized, controlled study was undertaken to determine whether combined use of interferon β‐1a (IFN) 30μg intramuscularly weekly and glatiramer acetate (GA) 20mg daily is more efficacious than either agent alone in relapsing–remitting multiple sclerosis. Methods A total of 1, 008 participants were randomized and followed until the last participant enrolled completed 3 years. The primary endpoint was reduction in annualized relapse rate utilizing a strict definition of relapse. Secondary outcomes included time to confirmed disability, Multiple Sclerosis Functional Composite (MSFC) score, and magnetic resonance imaging (MRI) metrics. Results Combination IFN + GA was not superior to the better of the single agents (GA) in risk of relapse. Both the combination therapy and GA were significantly better than IFN in reducing the risk of relapse. The combination was not better than either agent alone in lessening confirmed Expanded Disability Status Scale progression or change in MSFC over 36 months. The combination was superior to either agent alone in reducing new lesion activity and accumulation of total lesion volumes. In a post hoc analysis, combination therapy resulted in a higher proportion of participants attaining disease activity‐free status (DAFS) compared to either single arm, driven by the MRI results. Interpretation Combining the 2 most commonly prescribed therapies for multiple sclerosis did not produce a significant clinical benefit over 3 years. An effect was seen on some MRI metrics. In a test of comparative efficacy, GA was superior to IFN in reducing the risk of exacerbation. The extension phase for CombiRx will address whether the observed differences in MRI and DAFS findings predict later clinical differences. ANN NEUROL 2013;73:327–340